Hydroperiod and Salinity Interactions Control Mangrove Root Dynamics in a Karstic Oceanic Island in the Caribbean Sea (San Andres, Colombia) - Medina-Calderón, Jairo Humberto; Mancera-Pineda, José Ernesto; Castañeda-Moya, Edward; Rivera-Monroy, Víctor H. (Frontiers in Marine Science, 2021)
Mangroves sustain high soil accretion and carbon sequestration rates, yet it is still unknown if they can keep pace with increasing sea level rise (SLR) across a wider range of coastal geomorphic settings. Because accretion rates are controlled by mineral sediment inputs and organic matter accumulation, it is paramount to assess the relative contribution of root productivity to soil formation. Here, we evaluated root biomass, production, and turnover in three mangrove ecotypes to evaluate the role of soil nutrient limitation, stressors, and hydroperiod in controlling root dynamics in San Andres Island (SAI), a karstic oceanic island in the Caribbean Sea. Root growth was modulated by soil stress conditions and not by nutrient availability as it has been reported for other karstic environments. The lowest root biomass allocation, and both production and turnover of fine roots were measured under low flooding duration, and low salinity (< 20 PSU) and sulfide concentrations (0.84 ± 0.4 mM). Yet, when stress conditions increased during high flooding duration (6207 h y-1) and low oxygen conditions (Eh), root tissues reached the highest biomass and production values, including a relative fast turnover of fine roots (< 2 mm; 0.75 y-1). Our results follow the predictions of the plant root longevity cost-benefit hypothesis where plants maintain roots only until the efficiency of resource acquisition is maximized by water and nutrient acquisition. Because of the importance of groundwater in controlling porewater salinity and mangrove root productivity in karstic oceanic islands such as SAI, water use and coastal development should be regulated in the short term to avoid the loss of mangrove area and concomitant ecosystem services.